Geografias do Fogo e suas Territorialidades: um estudo na realidade Kalunga - Nádia Malena Moda (2024)
Fire is a disturbance and phenomenon that occurs on Earth, selects species and shapes environments and landscapes. It doesn't happen everywhere in the world, but where it occurs, the people who lived there, and still live, learned to use fire. With fire, they spread throughout the world and carried fire around the world, inhabiting environments and transforming landscapes. Thus, over time, it became a fundamental technique for maintaining life and survival, such as keeping warm, cooking food, hunting, cultivating plants and animals; Furthermore, it constitutes a fundamental part of cosmologies in different societies, composing the immaterial field of life, constituting territories and territorialities. From other views of nature, and through environmental policies, fire and its users have been criminalized in several countries, including Brazil, being a reason for dispute and a source of territorial conflicts. One of the people who use fire in various daily practices is the Kalunga quilombola people, who live mainly in the northeast of Goiás. In their demarcated territory, the Kalunga live with federal brigades from PrevFogo/IBAMA, which has other understandings about fire and its socio-ecological role. This research proposed, based on phenomenology, ethnogeography, fieldwork and open interviews, to understand the relationships between Prevfogo/IBAMA and the relationships between the Kalunga people and the territory based on fire management. From the narratives of the Kalunga people, it was possible to understand the role of fire in the production of space, its uses in agriculture and landscape management, symbolic meanings and the conflicts surrounding the different understandings between the Kalunga fire and the Institutional fire. Integrated Fire Management - as a policy and practice -, more than adding traditional knowledge in its conceptual formulation, must decolonize its way of acting, recognizing the autonomy of people in managing their territories.